RANCANG BANGUN APLIKASI MARKET PLACE UNIVERSITAS NEGERI SEBAGAI PERGURUAN TINGGI BERBADAN HUKUM - Basri, Irma Yulia; Ganefri, Ganefri; Yulastri, Asmar; Usmeldi, Usmeldi; Novaliendry, Dony; Giatman, Giatman (Jurnal Teknologi Informasi dan Pendidikan, 2023)
Regulation Government No. 114 of 2021 concerning Agency College _ Law University Padang State (UNP), on November 25, 2021 already official changed status to college high PTN-BH so that UNP can increase quality education . Government give autonomy to on UNP for increase its income generating . Since status service general (BLU), UNP has start commercialize means and existing infrastructure _ for Public general while facility that no disturb activity academic like pool swimming , building meeting , hotel, laboratory even so through activity training (CaKep , Pekerti). Commercialization services at UNP are still using the conventional system . Weakness existing system _ now is no all UNP Income Generating recorded by system , party user often experience difficulty for place an order because not yet existence facility service one door good physique nor integrated system . _ Difficulty user for make an order that is experienced during this because number contact personal contact no can direct obtained . UNP can maximizing Income Generating and enhancement effectiveness service to user through take advantage of digital technology and already should has its own marketplace platform . Article this aim for give ideas and the idea of designing a market place for PTN_BH UNP.